2006
DOI: 10.1182/blood-2005-08-3138
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the human T-cell leukemia virus (HTLV-1) tax-stimulated HIAP-1 gene for the survival of transformed lymphocytes

Abstract: IntroductionThe human T cell leukemia virus type 1 (HTLV-1) infection is causally linked with the development of a severe and fatal lymphoproliferative disorder of CD4 ϩ T cells, the adult T cell leukemia (ATL), and of the neurodegenerative disease HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). [1][2][3][4] Both diseases develop only after prolonged viral persistence. The HTLV-1 infection seems to stimulate growth and survival of the T-lymphocytes in carriers, since they expand to detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
54
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 77 publications
3
54
0
Order By: Relevance
“…45 Of note, this HTLV-1-stimulated, NF-kB-mediated abnormal expression of c-IAP2 contributes to the suppression of programmed cell death and supports the increased survival of HTLV-1-transformed lymphocytes. 45 This was demonstrated by RNA interference-mediated gene silencing of c-IAP2, which resulted in increased caspase activation and apoptosis along with reduced cell growth. 45 The prognostic significance of XIAP in acute myeloid leukemia (AML) has been controversially discussed.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…45 Of note, this HTLV-1-stimulated, NF-kB-mediated abnormal expression of c-IAP2 contributes to the suppression of programmed cell death and supports the increased survival of HTLV-1-transformed lymphocytes. 45 This was demonstrated by RNA interference-mediated gene silencing of c-IAP2, which resulted in increased caspase activation and apoptosis along with reduced cell growth. 45 The prognostic significance of XIAP in acute myeloid leukemia (AML) has been controversially discussed.…”
mentioning
confidence: 78%
“…In human T-cell leukemia virus type 1 (HTLV-1)-transformed adult T-cell leukemia, the viral oncoprotein Tax that is encoded by HTLV-1 aberrantly stimulates activation of the transcription factor NF-kB. 45 This in turn causes increased transcription of c-IAP2 as a prototype NF-kB target gene, leading to elevated protein expression of c-IAP2, a typical feature of adult T-cell leukemia. 45 Of note, this HTLV-1-stimulated, NF-kB-mediated abnormal expression of c-IAP2 contributes to the suppression of programmed cell death and supports the increased survival of HTLV-1-transformed lymphocytes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, RNAi-mediated knockdown of expression of the antiapoptotic protein HIAP1/CIAP2 induces apoptosis in HTLV-1-transformed T-cell lines. 35 The persistence of HTLV-1 in T-cell clones detectable over many years suggested that proteins mediating survival and growth of long-lived T cells could be crucial for HTLV-1 persistence and, thus, be potential targets of its oncoprotein Tax. Such properties are characteristic of the costimulatory receptor subgroup of the tumor necrosis factor receptor (TNFR) superfamily.…”
mentioning
confidence: 99%